MODEL OF ADAPTIVE CONDITION BASED TECHNICAL MAINTENANCE OF RADIOELECTRONIC TECHNOLOGY OBJECTS - Procenko, Ya.M. (Збірник наукових праць Військового інституту Київського національного університету імені Тараса Шевченка, 2017)
The article proposed adaptive strategy for condition based maintenance (ACTM) of complex objects of radioelectronic technology (RET), in which the frequency of the technical condition (TC) of the object is changed (corrected) during the operation, taking into account the current dynamics of the degradation processes in the apparatus. The basic idea of the ACTM strategy is that during each next control of the TC of the object (besides the maintenance) the forecast of reliability indices of its elements is adjusted, and according to the results of an adjusted forecast the time of the next control is calculated. The article reviews the algorithm of these calculations. The ACTM model is implemented in the framework of the simulation statistical model of the maintenance process and the RET objects repair. Through the application of the ACTM strategy, the obtained gain of the operation cost of the object is the greater (compared with the simple, not adaptive strategy), the greater is the value of the control TC of the object. The article gives an example of the strategy ACTM modelling.